Educoding: Media Pembelajaran Berbasis Website untuk Meningkatkan Kemandirian Belajar Siswa SMA - Salwa, Kemala Adinda; Bachri, Bachtiar Sjaiful; Kristanto, Andi (Akademika, 2024)
This study aims to measure the feasibility and effectiveness of EduCoding in improving students' learning independence in informatics subjects in high school. This study uses a Research and Development (R&D) model based on the Borg & Gall model which includes 10 stages. The study was conducted at SMA Negeri 3 Nganjuk with a sample of 36 students from Class X for each as an experimental and control class. The data collection instrument was a questionnaire for validation by media experts, material experts, and learning design experts to measure students' learning independence. The results showed that EduCoding was validated as "Very Valid" with a material score of 97% and media of 98%. The application of EduCoding in the experimental class showed a significant increase in learning independence compared to the control group. The posttest results showed a statistically significant difference (p <0.05) between the experimental and control classes, with students in the experimental group showing higher learning independence. EduCoding, equipped with features such as direct coding, structured materials, and interactive evaluations, effectively supports students in mastering computational thinking and encourages independent learning.